The Instructional Process: Cultivating Student Comfort to Optimize Effective Classroom Management - Ratu Talitha Ratu; Astuti Darmayanti (CV. Kayaswara, 2025)
The learning process in the classroom plays a crucial role in students' academic success. One of the main factors supporting this success is students' comfort while learning. This comfort is not only limited to physical aspects but also includes psychological and social factors that influence concentration and motivation. Therefore, good classroom management becomes a key element in creating a conducive learning environment. This article discusses various strategies that teachers can apply to enhance students' comfort, such as classroom arrangement, the use of engaging teaching methods, and the management of positive social interactions. By implementing these strategies, it is hoped that learning can be optimized, leading to the effective achievement of educational goals.